Asymmetric total synthesis of cephanolide B. Issue 3 (8th December 2020) - Zhang, Hongyuan; He, Haibing; Gao, Shuanhu
Abstract : The asymmetric synthesis of cephanolide B, a complex C18 Cephalotaxus dinorditerpenoid, is presented for the first time. Abstract : The asymmetric synthesis of cephanolide B, a complex C18 Cephalotaxus dinorditerpenoid, is presented for the first time. The synthesis relies on the key hexahydrofluorenone core skeleton (A-B-C ring). A remote hydroxyl group directed hydrogenation strategy was developed to selectively reduce the tetra-substituted enone unit. A sequence of modified transformations, including single electron reduction, Barton–McCombie radical deoxygenation, lactonization, and cation mediated Friedel–Crafts cyclization, were efficiently employed to achieve the target.